2022
DOI: 10.1111/gfs.12563
|View full text |Cite
|
Sign up to set email alerts
|

Yield, nutrient quality and water and phosphorus recovery efficiencies of alfalfa under different drip irrigation and phosphorus levels in Northern Xinjiang, China

Abstract: Rational water and fertilizer management have an important impact on alfalfa production. This research aimed to explore the effects of water and phosphorus (P) fertilizer on hay yield, nutrient quality, water-use e ciency (WUE) and phosphorus-recovery e ciency (PRE) of each cut of alfalfa under drip irrigation and to determine the best water and P interaction model for high quality and yield of alfalfa. In this study, different irrigation levels, i.e., 5.25, 6.0, and 6.75 ML ha -1 (referred to as W 1 , W 2 , W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…(2020). Our data were also consistent with P recovery ranges for other forages, such as mixed pastures of perennial ryegrass ( Lolium perenne L.) with white clover ( Trifolium repens L.) (8%–56%; Schils & Snijders, 2004) and alfalfa ( Medicago sativa L.) (7%–36%; Li et al., 2022).…”
Section: Discussionsupporting
confidence: 86%
“…(2020). Our data were also consistent with P recovery ranges for other forages, such as mixed pastures of perennial ryegrass ( Lolium perenne L.) with white clover ( Trifolium repens L.) (8%–56%; Schils & Snijders, 2004) and alfalfa ( Medicago sativa L.) (7%–36%; Li et al., 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Phosphorus in plants is highly mobile and allocation of P in plants is an important strategy for improving N and P utilization efficiency under nutrient deficiency ( Seleiman et al., 2020b ). Consequently, in alfalfa production, it is common to apply additional N and P fertilizers to increase yield and enhance quality ( Li et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a small portion of the applied P fertilizer is typically utilized by alfalfa. In that, a large portion of applied P fertilizer becomes fixed and accumulates in the soil profile, forming organic and insoluble inorganic P, which is difficult for alfalfa to directly absorb ( Li et al., 2022a ). Reduced soil P availability not only reduces alfalfa growth and quality, but also represents a significant economic and environmental challenge, relating to fertilizer and application costs, and surface and groundwater impairment ( Gu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Berg et al (2003) determined that approximately 70 kg ha -1 P fertilizer caused nearly 1 t ha -1 increment in annual dry matter production. In another research, Li et al (2022) determined that increasing P fertilizer increased the yield of alfalfa up to 100 kg ha -1 . According to Lissbrant et al (2009), a significant increment in alfalfa forage yield could be observed at 25 kg ha -1 P fertilization or more.…”
Section: Introductionmentioning
confidence: 99%